CREATING AUTHENTIC LEARNING ACTIVITIES IN PHARMACEUTICAL INSTRUMENTAL ANALYSIS: USING THE INTEGRATED LABORATORY NETWORK FOR REMOTE ACCESS TO SCIENTIFIC INSTRUMENTATION - Devon A. Cancilla; Simon P. Albon (Online Learning, 2019)
The Western Washington University Integrated Laboratory Network (ILN) is an initiative to provide anytime/anyplace access to scientific instrumentation for use in the classroom, laboratory, and research environments. The ILN provides students with greater opportunities to design and conduct real experiments remotely using advanced analytical instrumentation. This paper describes the use of the ILN to provide pharmaceutical sciences students at the University of British Columbia with remote access to instrumentation located at Western Washington University for the purpose of measuring metals in traditional herbal medicines. Prior to the introduction of the ILN, this type of activity would have been difficult, if not impossible, to conduct. Student feedback related to the use of the ILN was positive and supports the further development of curricular materials related to the use of remote instrumentation.